Role of autophagy-related proteins ATG8f and ATG8h in the maintenance of autophagic activity in Arabidopsis roots under phosphate starvation - Li-Yen Lin; Hong-Xuan Chow; Chih-Hao Chen; Nobutaka Mitsuda; Wen-Chun Chou; Tzu-Yin Liu; Tzu-Yin Liu (Frontiers in Plant Science, 2023)
Nutrient starvation-induced autophagy is a conserved process in eukaryotes. Plants defective in autophagy show hypersensitivity to carbon and nitrogen limitation. However, the role of autophagy in plant phosphate (Pi) starvation response is relatively less explored. Among the core autophagy-related (ATG) genes, ATG8 encodes a ubiquitin-like protein involved in autophagosome formation and selective cargo recruitment. The Arabidopsis thaliana ATG8 genes, AtATG8f and AtATG8h, are notably induced in roots under low Pi. In this study, we show that such upregulation correlates with their promoter activities and can be suppressed in the phosphate response 1 (phr1) mutant. Yeast one-hybrid analysis failed to attest the binding of the AtPHR1 transcription factor to the promoter regions of AtATG8f and AtATG8h. Dual luciferase reporter assays in Arabidopsis mesophyll protoplasts also indicated that AtPHR1 could not transactivate the expression of both genes. Loss of AtATG8f and AtATG8h leads to decreased root microsomal-enriched ATG8 but increased ATG8 lipidation. Moreover, atg8f/atg8h mutants exhibit reduced autophagic flux estimated by the vacuolar degradation of ATG8 in the Pi-limited root but maintain normal cellular Pi homeostasis with reduced number of lateral roots. While the expression patterns of AtATG8f and AtATG8h overlap in the root stele, AtATG8f is more strongly expressed in the root apex and root hair and remarkably at sites where lateral root primordia develop. We hypothesize that Pi starvation-induction of AtATG8f and AtATG8h may not directly contribute to Pi recycling but rely on a second wave of transcriptional activation triggered by PHR1 that fine-tunes cell type-specific autophagic activity.